Biogas production through mono- and co-digestion of pineapple waste and cow dung at different substrate ratios - Aili Hamzah, Adila Fazliyana; Hamzah, Muhammad Hazwan; Che Man, Hasfalina; Jamali, Nur Syakina; Siajam, Shamsul Izhar; Pau, Loke Show (Springer Nature, 2022)
The current study compares the biogas production via anaerobic co-digestion of pineapple waste and cow dung to mono digestion under mesophilic condition, with the goal of modifying the substrate ratio and increasing the system stability. Five different cow dung to pineapple waste ratios (1:1, 1:2, 1:3, 2:1 and 3:1) were assessed based on volatile solid (VS) contents. The highest biogas and methane yield were obtained at a ratio of 1:3 with 179.08 mL gas/g VS and 142.89 mL CH4/g VS, respectively. When compared to mono digestion of pineapple waste, the co-digestion process improved process stability in terms of C/N ratio, total ammonia nitrogen, VS removal and pH. Biogas refinement using carbon dioxide remover was able to reach high methane percentage while lowering carbon dioxide percentage to below 3%. The kinetic study using modified Gompertz model showed that the co-digestion process had shortened lag phase, and the highest biogas production rate was observed at 12.80 mL/g VS day. This suggests that the co-digestion process could increase biogas production rate, enhance process efficiency and significantly reduce fermentation time. Co-digestion of pineapple waste with cow dung appears to be a promising approach for bioenergy recovery.